Local event, family and music: The rootedness of cultural heritage - Gonçalves, A. (Family events: Practices, displays and intimacies, 2022)
By examining a singular case – the Rua Joaquina party in Lisbon (Portugal) – this chapter raises questions about the role of small-scale and locally based events in shaping feelings of togetherness, musical attachment and family affiliation. In particular, it explores how such events are meaningful settings for families, neighbours and their guests to meet up, jointly appreciate or perform music they value, and engage beginners in musical pathways. Accordingly, an approach of this kind also seeks to illustrate and understand the living aspects of cultural heritage. The used data came from long-term fieldwork conducted in Lisbon’s fado scenes.